HUBUNGAN ANTARA LAMA RAWAT DENGAN TINGKAT KECEMASAN KELUARGA PASIEN DI RUANG INTENSIVE CARE UNIT RSUD DR SOEKARDJO KOTA TASIKMALAYA - Rosidawati, Ida; Hodijah, Siti (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2019)
Intensive Care Unit (ICU) is a unit care of critical patients with mood in fast. The activity in an ICU is always busy and limited time visit, which find the family difficult to communicate with patient,while critically ill patients are usually treated for a long time, this can trigger families to experienced anxiety. The purpose of this research is to determine the relationship between length of stay and the level of anxiety family patients who being treated in dr. Soekardjo Tasikmalaya Hospital. This method of this research is used quantitative correlative with cross sectional approach. The sample of this research is family of patients who were waiting in the ICU room as many as 16 persons by using accidental sampling for two weeks. The data collected by using HARS scale and Chi Square analysis. The research result showed that patients with new length of stay ( mean = 3.81) as many as 7 people, families of patients not experiencing anxiety as many as 5 people (71%) and families who experienced anxiety as many as 2 people (29%). While patients with long duration of care (â‰¥ mean = 3.81) as many as 9 people, the patient's family all experienced anxiety (100%). Chi-square test result showed p-value of 0.005 Î± 0.05. The conclusion of the results of this study is that there is a relationship between length of stay with the level of anxiety of the patient's family, so it is recommended that the nurse or other medical team always coordinate with the family regarding the actions taken to the patient.Keywords: Intensive Care Unit (ICU), Long Care, Anxiety, Family Patients